2022
DOI: 10.3390/jof8040372
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion as a Focus in Trichoderma–Root Interactions

Abstract: Fungal spores, germlings, and mycelia adhere to substrates, including host tissues. The adhesive forces depend on the substrate and on the adhesins, the fungal cell surface proteins. Attachment is often a prerequisite for the invasion of the host, hence its importance. Adhesion visibly precedes colonization of root surfaces and outer cortex layers, but little is known about the molecular details. We propose that by starting from what is already known from other fungi, including yeast and other filamentous path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(80 reference statements)
0
7
1
Order By: Relevance
“…This finding concordanced to several researchers who also found Penicillium, Cylindrocarpon, Alternaria, Trichoderma, Cylindrocarpon, Phialophora, and Trichoderma in Verbenaceae family (De Siqueira et al 2011;Gong et al 2015;Singh et al 2017;Talita et al 2017;Vaz et al 2018;Tomy and Rakhra 2021). Some genera, such as Trichoderma, are specific for the roots and stems of the host plants (Habisukan et al 2021;Pescador et al 2022;Taylor et al 2022). Nonetheless, genera of Trichoderma in this study were found in leaf tissue of P. canescens.…”
Section: Isolation and Identification Of Endophytic Fungicontrasting
confidence: 53%
“…This finding concordanced to several researchers who also found Penicillium, Cylindrocarpon, Alternaria, Trichoderma, Cylindrocarpon, Phialophora, and Trichoderma in Verbenaceae family (De Siqueira et al 2011;Gong et al 2015;Singh et al 2017;Talita et al 2017;Vaz et al 2018;Tomy and Rakhra 2021). Some genera, such as Trichoderma, are specific for the roots and stems of the host plants (Habisukan et al 2021;Pescador et al 2022;Taylor et al 2022). Nonetheless, genera of Trichoderma in this study were found in leaf tissue of P. canescens.…”
Section: Isolation and Identification Of Endophytic Fungicontrasting
confidence: 53%
“…anisopliae and P. chlamydosporia are under development as bio-control agents for insecticide during agricultural production. , All these will complicate the components of mycotoxins for agricultural and food safety, due to not only the native production but also the inter-species bio-transformation. However, our work provided other possible solutions to re-evaluate the mycotoxins by examining the biosynthetic genes and/or expression to predict the mycotoxins.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chemical communication between fungi and plants is essential for interaction and diverse secondary metabolites are known to play an important role in this interplay (Macias-Rodriguez et al, 2020). Moreover, adhesion and the function of hydrophobins are required for plant-fungus interaction (Taylor et al, 2022). Intriguingly, stressed plants were found to secrete specific compounds attracting beneficial fungi (Lombardi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%